QUALITY OF LIFE DURING PREGNANCY: A COMPARATIVE STUDY BETWEEN URBAN AND RURAL AREAS IN INDONESIA - Nunik Puspitasari (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2023)
Assessing quality of life during pregnancy is vital to find timely preventive measures against pregnancy complications. The quality of life during pregnancy determines pregnant women’s health. This study aims to identify the differences in the quality of life during pregnancy who participated in antenatal care (ANC) visits in primary healthcare centers in rural and urban areas. This study used a cross-sectional design and collected data through  survey. The research population was 800 pregnant women who participated in ANC in three primary healthcare centers in urban areas and three others in rural areas. The quality of life during pregnancy questionnaire was used for data collection. The analysis was done using the Chi-square test and ordinal regression. Results showed no difference in the quality of life during pregnancy between women in urban areas and those in rural areas. Some factors that affected the quality of life during pregnancy included education, fetal age, number of pregnancies, number of live children, and pregnancy plans in women living in urban areas. Meanwhile, in women living in rural areas, the quality of life during pregnancy was affected by education level, occupation, fetal age, number of pregnancies, number of live children, and pregnancy plans. There are influences of age, education level, occupation, gestational age, number of pregnancies, number of living children, and pregnancy plans on the quality of life of pregnant women in rural areas.